2016
DOI: 10.1002/2015ja022056
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial vertical drift modulation by the lunar and solar semidiurnal tides during the 2013 sudden stratospheric warming

Abstract: During the 2013 stratospheric sudden warming (SSW) period the Jicamarca Unattended Long‐term Investigations of the Ionosphere and Atmosphere (JULIA) radar at Jicarmarca, Peru, observed low‐latitude vertical drift modulation with lows of 0–12 m/s daytime maximum drifts between 6–13 and 22–25 January and enhanced drifts up to 43 m/s between 15 snd 19 January. The NCAR thermosphere‐ionosphere‐mesosphere‐electrodynamics general circulation model reproduces the prevailing vertical drift feature and is used to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…These amplifications are evident in ground‐based radar data (Fejer et al, , ; Stening & Fejer, ) and magnetic field perturbations associated with the EEJ (Park et al, ; Stening, ; Yamazaki, ; Yamazaki et al, ). Many aspects of these SSW responses have been captured by first‐principles general circulation models of the whole atmosphere‐ionosphere system (Maute et al, ; Pedatella, Liu, Richmond, Maute et al, , ), which have also provided new physical insights and corroborated prior interpretations. The development of these models is a second major development that has enhanced our study of the lunar ionospheric tide.…”
Section: Introductionmentioning
confidence: 81%
“…These amplifications are evident in ground‐based radar data (Fejer et al, , ; Stening & Fejer, ) and magnetic field perturbations associated with the EEJ (Park et al, ; Stening, ; Yamazaki, ; Yamazaki et al, ). Many aspects of these SSW responses have been captured by first‐principles general circulation models of the whole atmosphere‐ionosphere system (Maute et al, ; Pedatella, Liu, Richmond, Maute et al, , ), which have also provided new physical insights and corroborated prior interpretations. The development of these models is a second major development that has enhanced our study of the lunar ionospheric tide.…”
Section: Introductionmentioning
confidence: 81%
“…[], and Maute et al . [] found that the lunar tide can have amplitude similar to the tide produced by solar heating. TMAT is unable to resolve the small difference in frequency between lunar and solar tides, and the SW2 estimate would include a superposition of both tides.…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that stratospheric sudden warming events produce favorable conditions for the vertical propagation of the M 2 tide from the lower atmosphere to the upper atmosphere, which results in an amplification of the M 2 tide in the lower thermosphere. Simulations based on coupled thermosphere‐ionosphere models have demonstrated that the enhanced M 2 tide during stratospheric sudden warming events can produce large perturbations in the equatorial electric field (Maute et al, ; Pedatella & Liu, ; Pedatella, Liu, Richmond, et al, ; Pedatella et al, , ).…”
Section: Introductionmentioning
confidence: 99%